2021
DOI: 10.48550/arxiv.2111.09655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of the U.S.--China Trade War on Stock Markets: A Financial Contagion Perspective

Abstract: In this paper, we investigate the effect of the U.S.-China trade war on stock markets from a financial contagion perspective, based on high-frequency financial data. Specifically, to account for risk contagion between the U.S. and China stock markets, we develop a novel jump-diffusion process. For example, we consider three channels for volatility contagion-such as integrated volatility, positive jump variation, and negative jump variation-and each stock market is able to affect the other stock market as an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To account for the whole-day market dynamics, Kim and Wang (2021) (Kim and Wang, 2021). Recently, to anaylze the risk contagion between the U.S. and China stock markets, Oh and Kim (2021) proposed the overnight diffusion process, which can accommodate the fact that volatility transmission occurs through overnight volatility processes. In financial applications, we are often required to explore the dynamics of the correlations among assets, which leads us to extend the univariate overnight GARCH-Itô model to a multivariate form.…”
Section: Introductionmentioning
confidence: 99%
“…To account for the whole-day market dynamics, Kim and Wang (2021) (Kim and Wang, 2021). Recently, to anaylze the risk contagion between the U.S. and China stock markets, Oh and Kim (2021) proposed the overnight diffusion process, which can accommodate the fact that volatility transmission occurs through overnight volatility processes. In financial applications, we are often required to explore the dynamics of the correlations among assets, which leads us to extend the univariate overnight GARCH-Itô model to a multivariate form.…”
Section: Introductionmentioning
confidence: 99%
“…In this empirical study, we do not consider the robustness of jumps.18 We notice thatOh and Kim (2021) study the U.S.-China trade war based on a volatility contagion model, and the model is estimated by QMLE. The PaReMeDI estimator is used as an alternative measure of IV, and it is found that the QMLE and PaReMeDI estimates are quite close.19 Note that Aït-Sahalia and Jacod (2014) andLi et al (2022) only consider the regular observation scheme.…”
mentioning
confidence: 99%